Hydrogen On Track. - Jones, W.D.
This paper discusses the latest developments in the field of hydrogen-fuel cell propulsion research for application in the rail transportation and heavy industry. These include the ongoing project at Vehicle Projects LLC to retrofit a 109-metric ton diesel electric yard switcher locomotive with a powertrain that features polymer electrolyte membrane (PEM), hydrogen fuel cell stacks. Hydrogen-fueled trains are also being planned for a 59-km long commuter rail line in Denmark and for the 48-km long freight line in North Carolina that is scheduled for conversion into a commuter rail connection by 2009. Hydrogen is also proving to be the fuel of choice for other industrial purposes such as for standby power, airport baggage tractors, forklifts, and shuttle buses
Keywords: 48 km; 59 km; Denmark; North Carolina; PEM; Vehicle Projects LLC; Commuter rail line; Diesel electric yard switcher locomotive; Heavy industry; Hydrogen fuel cell stacks; Hydrogen-fuel cell propulsion research; Polymer electrolyte membrane; Powertrain; Rail transportation